A study on the abundance of zooplankton of a culture and a non-culture pond of the Rajshahi University campus (University Journal of Zoology, Rajshahi University, 2009)
Zooplankton constitute important food item of many omnivorous and carnivorous fishes. The study was conducted with an aim to study the zooplankton production including physico-chemical parameters with an emphasis to the existing management practices taken by the operators. The study was carried out in a culture and a non-culture pond of Rajshahi University campus was carried out from September, 2004 to February, 2005. Monthly fluctuations of some physico-chemical parameters were noted. The ponds showed alkaline in nature with moderate bicarbonate alkalinity. Diurnal change of water temperature, free CO2 and dissolved Oxygen were also studied. Four groups of zooplankton were identified, of which copepods (1260 units/l and 973.33 units/l in pond-1 and pond-2 respectively) were most dominant. A total of 9 genera of zooplankton were identified of which Cyclops (68.25% and 60.28% of total copepods) was most abundant in both ponds. Total zooplankton showed positive correlation with pH, carbonate alkalinity (CO3) and bicarbonate alkalinity (HCO3) in both ponds and DO, carbon dioxide (CO2) in pond-1. Present findings indicated that the culture pond showed better result than that of the non-culture pond regarding zooplankton production. Key words: Zooplankton, culture pond, non-culture pond, physico-chemical parameters. Â  doi:10.3329/ujzru.v27i0.1951 Univ. j. zool. Rajshahi Univ. Vol. 27, 2008 pp. 35-41